Designer co-beta-peptide copolymer selectively targets resistant and biofilm Gram-negative bacteria. (March 2023) - Si, Zhangyong; Li, Jianguo; Ruan, Lin; Reghu, Sheethal; Ooi, Ying Jie; Li, Peng; Zhu, Yabin; Hammond, Paula T.; Verma, Chandra S.; Bazan, Guillermo C.; Pethe, Kevin; Chan-Park, Mary B.
Abstract: New antimicrobials are urgently needed to combat Gram-negative bacteria, particularly multi-drug resistant (MDR) and phenotypically resistant biofilm species. At present, only sequence-defined alpha-peptides ( e.g. polymyxin B) can selectively target Gram-negative bacterial lipopolysaccharides. We show that a copolymer, without a defined sequence, shows good potency against MDR Gram-negative bacteria including its biofilm form. The tapered blocky co-beta-peptide with controlled N-terminal hydrophobicity (#4) has strong interaction with the Gram-negative bacterial lipopolysaccharides via its backbone through electrostatic and hydrogen bonding interactions but not the Gram-positive bacterial and mammalian cell membranes so that this copolymer is non-toxic to these two latter cell types. The new #4 co-beta-peptide selectively kills Gram-negative bacteria with low cytotoxicity both in vitro and in a mouse biofilm wound infection model. This strategy provides a new concept for the design of Gram-negative selective antimicrobial peptidomimetics against MDR and biofilm species.